Research progress in the relationship between packaging structures and service performance of MEMS inertial sensors - Liu, Zhaoyang; Yang, Xu; Jia, Yongjun; Zhang, Yanshun; Pang, Yang; Huang, Xiaojuan (Frontiers in Materials, 2025)
In recent years, micro-electro-mechanical systems (MEMS) technology has advanced rapidly, leading to widespread adoption of MEMS inertial sensors in areas such as consumer electronics, industrial automation, national defense, and military systems. These sensors offer notable advantages, including compact size, low cost, and ease of large-scale production. This study provides a comprehensive review of recent research, both domestic and international, focusing on how variations in packaging design affect the performance of MEMS inertial sensors across consumer-grade, industrial-grade, and tactical-grade classifications. Typical sensor models, including the MPU9250, ADIS16470, and the tactical-grade HG1930, are selected as representative examples. The influence of different packaging types—such as quad flat no-lead (QFN), ceramic leadless chip carrier (LCC), and hermetic metal vacuum packaging—on key performance metrics such as bias stability, noise density, and temperature drift is analyzed in depth. Moreover, the influence mechanism of electronic packaging design on inertial sensors is explained from the perspective of the coupling of thermal-mechanical-electrical multi-physics models. Finally, this paper explores the development potential of emerging packaging technologies, including heterogeneous integration, intelligent compensation, and quantum-level techniques, in driving future performance breakthroughs in MEMS inertial sensors.